Origin and development of alimentary habits and customs as a sociocultural resource for mankind: an approach to history and anthropology of care with regard to alimentation - Manuel Lillo Crespo; María Flores Vizcaya Moreno (Cultura de los Cuidados, 2012)
Amongst all creatures on earth, man is the only one that has a "sense of destiny" and is able to symbolise even what appears to be strictly physical and material objects or phenomena. Therefore, any food -fruits, vegetables, pulses, fish- can possess various symbolic values according to different cultures and eras. The characteristics that link mankind with animals, and the social organisations and abilities developed long ago constitute a precious legacy which -in slow, quiet but constant evolution- have survived until present. The role that food has played within human diet, the involuntary nutrition process and the conscious feeding action is approached here from an anthropological point of view, following a clear historic view. The main objective of this work is to show the way in which the social and symbolic value of food through history in different cultures has survived, where its starting point is located, and the foundations on which its essence with regard to care leans.